It's Tough To Be a Critic: Professional Versus Nonprofessional Music Judgment. (July 2017) - Lundy, Duane E.; Smith, Josh L.
Potential differences between professional critics' and nonprofessional undergraduates' aesthetic appraisals in music were investigated via intercorrelations and frequency distributions of ratings. As expected, for 50 randomly selected albums, professional critics ("experts") who had previously rated these albums showed highly consensual ratings ( r  =+.61, p  < .0005), as well as mound-shaped distributions approaching normality (i.e., the majority of ratings near neutrality and fewer scores at greater extremes). In contrast, 15 nonprofessionals' rating distributions ("nonexperts") for the same sample of albums varied more from mound-shaped distributions compared with the professional critics. Also, none of the nonprofessionals' ratings were correlated with the critics' ratings, and relatively few of the nonprofessionals' ratings were correlated with each other (average r  =+.08, N  = 105 pairs). The philosophy that beauty is completely in the eye of the beholder, at least for music perception, was only empirically supported in the case of nonprofessional, nonexpert judges.